EIB Investment Survey 2021 - EU overview - European Investment Bank (European Investment Bank, 2021)
This unique insight into the corporate investment landscape in the European Union examines companies' finance needs and the constraints they face. The 2021 edition delves into the massive shock produced by the COVID-19 crisis, and the response and recovery programmes put in place by the European Union and by national governments. The report assesses the extent to which European firms are addressing the need make their businesses more green and digital. The survey is based on interviews with 12 000 companies across the 27 European Union countries, and it includes a benchmark sample from the United Kingdom and United States. This overview provides the aggregated results for the European Union. Results for individual countries will be published in January 2022.